Structure-based discovery of novel 4, 5, 6-trisubstituted pyrimidines as potent covalent Bruton's tyrosine kinase inhibitors. Issue 13 (1st July 2016) - Zou, Yi; Xiao, Jianhu; Tu, Zhengchao; Zhang, Yingyi; Yao, Kun; Luo, Minghao; Ding, Ke; Zhang, Yihua; Lai, Yisheng
Graphical abstract: Abstract: A series of novel 4, 5, 6-trisubstituted pyrimidines were designed as potent covalent Bruton's tyrosine kinase (BTK) inhibitors based on the structure of ibrutinib by using a ring-opening strategy. Among these derivatives, compoundI1 exhibited the most potent inhibitory activity with an IC50 value of 0.07 μM. The preliminary structure–activity relationship was discussed and the primary amino group at the C-4 position of pyrimidine was crucial for maintaining BTK activity. Furthermore, molecular dynamics simulations and binding free energy calculations were performed for three inhibitor-BTK complexes to determine the probable binding model, which provided a comprehensive guide for further structural modification and optimization.